Posttraumatic Stress Disorder and Risk for Early Incident Atrial Fibrillation: A Prospective Cohort Study of 1.1 Million Young Adults. Issue 19 (1st October 2019) - Rosman, Lindsey; Lampert, Rachel; Ramsey, Christine M.; Dziura, James; Chui, Phillip W.; Brandt, Cynthia; Haskell, Sally; Burg, Matthew M.
Abstract : Background: Acute psychological stress and negative emotions are known risk factors for atrial fibrillation (AF). Whether exposure to chronic stress syndromes, such as posttraumatic stress disorder (PTSD), also increases susceptibility to AF is unknown. Methods and Results: We prospectively assessed the incidence of AF over a 13‐year period among 988 090 young and middle‐aged veterans (mean age, 30.29±9.19 years; 87.8% men, 64.5% white) who first accessed care through the Veterans Health Administration from October 2001 to November 2014 and were free of AF, atrial flutter, or atrial tachycardia at baseline. Time‐varying, multivariate Cox proportional hazard models were used to examine the independent contribution of PTSD to new AF. We also tested for effect modification by sex and controlled for healthcare use. During a mean follow‐up of 4.8 years, 2491 patients were diagnosed with AF. Patients with PTSD had a higher overall incidence of AF ( P <0.0001) and were more likely to develop AF at a younger age than those without PTSD ( P =0.004). PTSD was significantly associated with incident AF in unadjusted models (hazard ratio, 1.31; 95% CI, 1.19–1.43) and models that adjusted for demographics, lifestyle factors, cardiovascular risk factors, and depression (hazard ratio, 1.13; 95% CI, 1.02–1.24). The interaction with sex was nonsignificant ( P =0.93). Conclusions: PTSD was associated increased risk for early incident AF after adjustment for established AF risk factors and depression in this cohort of young and middle‐aged veterans. Findings from this study require validation in more diverse populations to determine their generalizability.